Development of smart bio-polymeric nanostructures for stimuli-response based applications - Hawkins, Bradley Robert (Curtin University, 2014)
Biodegradable polymers are a rising commodity in the polymer industry, offering a resolution to disposal and environmental concerns. Biocompatibility within these types of polymers has resulted in extensive research towards medical applications. This research explores the development of smart bio-polymeric nanostructures by a low-cost manufacturing process known as electrospinning. Specific polymers were selected for this work to provide a stimuli-responsive system that is applicable for a range of applications.